Biomarkers of oral exposure to 3-nitro-1, 2, 4-triazol-5-one (NTO) and 2, 4-dinitroanisole (DNAN) in blood and urine of rhesus macaques (Macaca mulatta). (November 2013) - Hoyt, Nathan; Brunell, Marla; Kroeck, Karl; Hable, Mike; Crouse, Lee; O'Neill, Art; Bannon, Desmond I.
Abstract The U.S. Department of Defense is using the chemicals 2, 4-dinitroanisole (DNAN) and 3-nitro-1, 2, 4-triazol-5-one (NTO) in new munitions development. In a screen for biomarkers of exposure, these compounds were measured in urine and blood of male rhesus monkeys after oral doses. NTO peaked at 4 h, with urinary concentrations at least 100-fold higher than that of blood or serum while 4-dinitrophenol (DNP), a metabolite of DNAN, appeared in blood at concentrations 10- to 20-fold higher than the parent compound. For human exposure monitoring, urine is optimal for NTO while the metabolite DNP in blood is best for DNAN.